The effect of a perceptual-motor training programme on the coincident anticipation timing and batting performance of club cricket players - Van Velden, Grant David (Stellenbosch : University of Stellenbosch, 2010)
Thesis (M Sport Sc (Sport Science)-- University of Stellenbosch, 2010.